Camarillo Airport Authority/Oxnard Airport Authority Minutes - Michael A. Musca:::::: (1998)
The minutes of a meeting between the Camarillo Airport Authority and the Oxnard Airport Authority. Discusses the meeting plans, hangar development, community relations, personal classifications, and airport noise.